O ciclo de vida profissional dos professores de Biologia da Universidade Federal de Uberlândia: trajetórias, carreira e trabalho - Brito, Talamira Taita Rodrigues (2011)
This research approaches the studies on the university teaching. The following questions guided the development of the work: how do teachers of the Biology Institute of the Federal University at Uberlândia build their cycles of professional life from their training bases and work? What meanings are generated about career, profession, and work, from the relationship with their historical condition of personal and professional life? How/when does the process of recognition of being a teacher in the professional journey in college occur? The research objectives were: to understand how these teachers build their Professional Lifecycle; to verify how the idea of the teaching career has been consolidated from the relationships among work, subject, and university; to analyze how the process of recognition of the professional journey in being a teacher at the university take place. The methodology supporting the work was the thematic oral history. The thematic interview was our interlocution media with the six subjects of the research and showed among other things, that in their perceptions, the career is strange to their professional status. When deciding to become teachers in public universities, they opt to meet a prescribed career, which identifies, qualifies and distinguishes them from other professionals. There is clarity among the oldest about the processes of intensification of the teachers' work within the university. For the younger ones, both the burden of coming up with the recent title of doctor and having to work, besides producing in the same way as a teacher with years of experience is something that expresses a lack of political definition of roles for those who already are in the university, and for those arriving as well. We could understand both through the dialogue between the studies about the field and the narratives of the teachers who construct day by day their trajectory linked to their careers that there is a life cycle happening individually and collectively at the same time. The research group, according to the service affiliation presented four stages of their professional career. Most of them focused on the doctorate as an important change of meaning in teaching and being a teacher as well, for that title is related to the academic sense of autonomy.